Financial Inclusiveness in Islamic Banking in Pakistan: A Comparison of Ideas and Practices - Shaikh, S. A. (Universiti Sains Islam Malaysia, 2024)
This study attempts to document the progress in Islamic banking industry of Pakistan towards fostering an egalitarian and equitable financial intermediation. It evaluates the progress of Islamic banking in enhancing socio-economic mobility, financial inclusiveness and fostering equitable distribution of income. This study uses a set of quantitative indicators to objectively assess the performance of Islamic banks towards fostering a participative, inclusive, cost-effective and real sector oriented financial intermediation. The results highlight that currently, the performance of Islamic banks on these fronts leaves much to be desired. This study highlights that high average cost of financing and limited focus on agriculture and small and medium enterprises requires improvement to achieve the goal of circulation of wealth and equitable distribution of income. It also identifies that various categories of poor people who need finance for their health, education and small business working capital needs cannot be served by Islamic banks by using the available product structures. This study gives a geographical presence of Islamic banks which shows that they are mainly based in big urban cities. It argues that most of the Islamic banking debt-based products are close, but relatively expensive substitutes. The study will help the industry to review its performance in contributing towards financial inclusiveness, social mobility, need fulfillment and equitable income distribution.